Examining the role of early bilingualism on interference suppression and prefrontal connectivity - Cook, Matthew L.; Boyce, Lisa K.; Hancock, Allison S.; Turner, Makenzy S.; Bradshaw, Spencer D. (Frontiers in Integrative Neuroscience, 2025)
Inhibitory control is a core cognitive function that is primarily associated with activation in the prefrontal cortex (PFC) and is the cognitive function that inhibits impulses, thoughts, and suppresses irrelevant information to an identified goal or task. Prior research suggests that bilingualism may affect brain activity related to inhibitory control, yet few studies have compared functional activity between monolingual and bilingual children. The current study used functional near-infrared spectroscopy (fNIRS) to examine region of interest comparisons and task-state functional connectivity across the PFC during an interference suppression Simon task with 13 bilingual (East Asian or Ibero-romance paired with English) and 13 age-matched English monolingual preschoolers. Results showed no significant differences in behavioral measures of interference suppression. However, bilingual preschoolers showed lower oxygenated hemoglobin activation and more localized patterns of connectivity within the PFC, suggesting more efficient processing during suppression compared to their monolingual peers. This may reflect the bilingual experience of regularly suppressing their second language when not in use, thus facilitating neural efficiency. These findings contribute to the growing body of literature on bilingual cognitive development suggesting that functional connectivity during executive function may differ in bilingual children, even at a young age, despite no observable behavioral differences. This highlights the importance of integrating neuroimaging with behavioral data to gain a more comprehensive understanding of bilingual cognitive development.